Implementasi Kebijakan Penanganan Kawasan Kumuh Di Kecamatan Mariso Kota Makassar - Anita, Andi Dwi Aprial; Said, Alimuddin; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to find out how the organizational behavior affects successful implementation of slum management policies in Mariso District, Makassar City. This study used qualitative with descriptive research type. the number of informants was 3 people. Data collection techniques used  interviews and observations of a number of informants. The results showed that the implementation process of slum management policies measured using indicators consisting of inter-organizational relationship behavior, lower-level implementor (apparatus) behavior and target group behavior was good. However, the behavioral indicators had not been implemented properly, it was necessary to adjust according to the vision and mission in the office so that it was carried out properly and for the target group the impact of the implementation of slum management was not evenly distributed because there were some people refused the implementation of handling slum areas resulting in some areas that were not handled.Keywords: Policy implementation, slum management